Pengembangan Motorik Halus Anak Melalui Kegiatan Bermain Kolase Pada Kelompok B di TK Masmur Teratak Buluh - Rizka Fajriyenni (Jurnal Pendidikan Tuntas, 2025)
This study was motivated by the low level of fine motor development among children in Group B at Masmur Kindergarten, located in Teratak Buluh, Kampar Regency. The researchers considered this to be an important issue that needed to be addressed immediately, as children's fine motor skills affect other aspects of their development. Fine motor skills are movements that involve only certain parts of the body and are performed by small muscles, such as the ability to use the fingers and wrist movements. The activity used in this study was beading, which is defined as a technique of attaching various elements into a single frame to produce a new work of art. The research method applied is the classroom action research method, which is carried out in two cycles, each consisting of two meetings or face-to-face sessions. while there are four stages in each cycle, including: the preparation stage, the implementation stage, the observation stage, and the reflection stage. The data collection techniques used are observation and documentation, while the data analysis techniques are quantitative and qualitative techniques. The results showed that collage activities were proven to improve the fine motor skills of children in group B at Masmur Teratak Buluh Kindergarten. This was evident from the learning achievements of students before the cycle, where 7 children were below the standard, 0 children in cycle I, and 0 children in cycle II. while MB pre-cycle was 2 children, cycle I became 4 children and cycle II became 0 children. For BSH pre-cycle, there were 2 children, cycle I became 6 children and cycle II became 1 child. Finally, the BSB score in the pre-cycle was 0 children, cycle I became 1 child and cycle II became 10 children. The conclusion shows that collage activities can improve children's fine motor skills.